Disseminated primary herpes simplex infection imitating preterm prelabor rupture of membranes - a case report - Dylan Campbell; Henry Lesser; Robert M. Ehsanipoor (Elsevier, 2023)
Background: We describe a case of primary herpes simplex virus (HSV) infection imitating preterm prelabor rupture of membranes (PPROM) and review the intricacies of establishing the diagnosis. Case presentation: At 18 weeks of gestation, a patient was referred for suspected PPROM following leakage of fluid and a positive nitrazine test. The patient had a swollen inguinal lymph node, intermittent fevers, transaminitis, labial lesions, and cervical ulceration with vaginal discharge. Amniotic fluid volume was normal. An HSV PCR test was positive. Intravenous acyclovir followed by oral valacyclovir resulted in resolution of symptoms. Conclusion: Discharge from HSV cervicitis can present as nitrazine-positive pooling, imitating PPROM. A high index of suspicion is warranted, especially when the amniotic fluid volume is normal and arborization is not seen on microscopic exam.